INVESTIGATING THE LEVEL OF BURNOUT AND INFLUENCING FACTORS ON IT AMONG THE WORKERS: CASE STUDY THE PETROCHEMICAL INDUSTRIES NATIONAL COMPANY - Hassan DARVISH; Ahmad ZARE; Hamid Hosseinzadeh NEKOIE (Management & Marketing, 2011)
This study is done with the purpose of investigation the level of burnout andinfluencing factors on it. The method used is measuring or filed-finding,descriptive studies type and the statistic society is made of the entire officialand non-official workers in the petrochemical industries national company inthe year (2009) including 6901people in the main office and 12 subsidiarycompanies who are working. The estimation of the sample volume is madeusing the cochran formula by the volume of 1742 people and the accidentalclass and the domesticated form of the Maslach Burn Out Inventory has beenused for gathering the dependant variant data of the study. In this study therelevance or effect of 20 independent variables on the burnout and itsconstituents was investigated. In the two variable tests, the emotionalcommitment had a reverse relation with burnout. So that with the increase ofthe interest and bind of the workers to the organization, the level of burnoutdecreased. In analyzing the step by step regression of the burnout accordingto the expected variables, 41percent of the explained burnout (R 2 =41%),and ranking the amount of the standard coefficient, the main elements likethe nature of the job, emotional commitment, work environment, job security,coworkers, education, job type, salary and the premium and jobindependence in the remaining regression equation and on the burnoutvariable have been influencing.